SYSTEM ADMINISTRATION SERVICES COMPANY LAUNDRY / DRY CLEANING PUSPA INDAH USING MICROSOFT VISUAL BASIC 6.0 - Dedi Junaedi; Cut Asiana Gemawaty, SKom., MMSI Cut Asiana Gemawaty, SKom., MMSI (Jurnal Sistem Informasi, 2005)
Administrative system is so decisive in the smoothness of a business, because to advance a business one should be supported by robust administrative system, fast, effective and efficient. System administration manual handling is actually very inviting too much risk losing data and documents that are essential to enterprise and handling is still slow, so would hamper the work of other systems. So the writer tries to apply the administrative system by using computers to help facilitate the administrative process laudry services more quickly, effectively and efficiently.